The Effect of the Use of the Beneficial Acetic Acid Bacteria Starter Cultures on the Microbiological and Physicochemical Quality of Raw Ripening Sausages - Anna Okoń; Anna Łepecka; Piotr Szymański; Katarzyna Neffe-Skocińska (Applied Sciences)
The aim of the study was to assess the possibility of using novel Gluconobacter oxydans strains in the technology of raw ripening sausages and to assess their impact on the microbiological and physico-chemical quality after production and after 6 months of storage process. Four variants of sausages were prepared: two control sausages (with salt and with curing salts addition), and two study variants with different acetic acid bacteria starters addition. Microbiological and physicochemical analyses were carried out. All variants of study sausages showed good microbiological quality concerning the total number of microorganisms, lactic acid bacteria, and the absence of pathogenic microorganisms. The synergistic effect of lactic acid bacteria and acetic acid bacteria was observed and a positive effect on the survivability of the native lactic microbiota of study sausages was shown. It was shown that sausage with the addition of acetic acid bacteria (AAB) strains were characterized by higher antioxidant properties compare to control samples. These results were confirmed by the analysis of oxidation–reduction potential and lipid oxidation products, which showed low oxidation–reduction potential (ORP value) and amounts of malondialdehyde (MDA) in the study products. Based on the obtained results of microbiological and physicochemical analysis, the technological usefulness of the study AAB strains, as starter cultures for the production of raw ripening meat products, was demonstrated.